2011
DOI: 10.1109/tpwrs.2010.2082576
|View full text |Cite
|
Sign up to set email alerts
|

Robust Transmission Network Expansion Planning Method With Taguchi's Orthogonal Array Testing

Abstract: This paper proposes a robust transmission network expansion planning (RTNEP) method with Taguchi's orthogonal array testing (TOAT) which considers generation dispatch and operating uncertainties caused by load demand and renewable energy output. TOAT is a method which has been proven to be optimal to select representative scenarios for testing from all the possible combinations. This paper employs TOAT to determine testing scenarios in transmission network expansion planning (TNEP). A new RTNEP formulation is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
93
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(93 citation statements)
references
References 17 publications
0
93
0
Order By: Relevance
“…In Type I, worst-case uncertainty scenarios are incorporated into the problem. Taguchi's orthogonal array testing (TOAT) [12] is used for that purpose. In type II [13], for each uncertain parameter an allowable range is specified, and then the problem is solved while the uncertainty is bound in the specified range.…”
Section: Indicesmentioning
confidence: 99%
“…In Type I, worst-case uncertainty scenarios are incorporated into the problem. Taguchi's orthogonal array testing (TOAT) [12] is used for that purpose. In type II [13], for each uncertain parameter an allowable range is specified, and then the problem is solved while the uncertainty is bound in the specified range.…”
Section: Indicesmentioning
confidence: 99%
“…By incorporating the typical scenario set, the classical multi-scenario TNEP model is formulated by [6,8]: The objective of Equation (11) is to find the minimum cost planning scheme that satisfies the load demand and renewable power consumption in all typical scenarios. It can be observed that a sufficiently large penalty factor β can effectively drive both the load shedding and renewable generation curtailment to zero.…”
Section: Classical Multi-scenario Tnep Modelmentioning
confidence: 99%
“…[7] applied the Monte Carlo simulation (MCS) to simulate the uncertainties of outages and load forecasting in the coordinated generation-transmission expansion planning. In addition, the robust TNEP design based on extreme scenarios was adopted by [8,9] to improve the robustness of planning schemes. Nevertheless, the above multi-scenario methods still have limitations, as they tend to generate a large number of scenarios to achieve accurate simulation of uncertainties, which may cause a heavy computational burden.…”
Section: Introductionmentioning
confidence: 99%
“…If the system is large, the computational burden may become too heavy to be tolerated. Hence, we employ the Taguchi's orthogonal array testing (TOAT) [19] with the probability re-assignment that developed in our study for reducing information redundancy, as given below:…”
Section: Scenario Synthesis and Redundancy Reductionmentioning
confidence: 99%
“…Step 3: Construct the orthogonal arrays (OAs) [19] in a size of m rows and n columns, where m is the number of refined scenarios generated by the TOAT and n is the number of uncertain variables input from Step 2. m is much smaller than the number of initial scenarios, and they are regarded as the representative scenarios while preserving good statistical information.…”
Section: Scenario Synthesis and Redundancy Reductionmentioning
confidence: 99%